2019
DOI: 10.1063/1.5054721
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced near-infrared electroluminescence from a neodymium complex in organic light-emitting diodes with a solution-processed exciplex host

Abstract: We report the enhanced near-infrared (NIR) electroluminescence from a Nd 3+ -complex with thenoyltrifluoroacetone and 1,10phenanthroline ligands. The NIR-emitting complex was blended into an exciplex-forming co-host system comprising 2,7bis(diphenylphosphoryl)-9,9'-spirobifluorene as the electron transport material and 4,4',4"-tris(carbazol-9-yl)triphenylamine as the hole transport material, in solution-processed small molecule organic light-emitting diodes (OLEDs). This binary ambipolar host system favors dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…The PLQY of Nd‐6 doped film was about 0.5%, and the optimized device ITO/PEDOT:PSS/mCP: Nd‐6 /TPBi/LiF/Al exhibited a maximum EQE of 0.022%. And in 2019, the authors changed the host materials of this device. With a structure of ITO/PEDOT:PSS/TCTA:SPPO13 (2,7‐bis(diphenylphosphoryl)‐9,9′‐spirobifluorene): Nd‐6 /TPBi/LiF/Al, the device reached a maximum EQE of 0.034%, which was more superior to the best value of solution‐processed NIR OLEDs and comparable to the best evaporation‐processed NIR OLEDs …”
Section: Nir Light Emission Lanthanide Complexesmentioning
confidence: 99%
“…The PLQY of Nd‐6 doped film was about 0.5%, and the optimized device ITO/PEDOT:PSS/mCP: Nd‐6 /TPBi/LiF/Al exhibited a maximum EQE of 0.022%. And in 2019, the authors changed the host materials of this device. With a structure of ITO/PEDOT:PSS/TCTA:SPPO13 (2,7‐bis(diphenylphosphoryl)‐9,9′‐spirobifluorene): Nd‐6 /TPBi/LiF/Al, the device reached a maximum EQE of 0.034%, which was more superior to the best value of solution‐processed NIR OLEDs and comparable to the best evaporation‐processed NIR OLEDs …”
Section: Nir Light Emission Lanthanide Complexesmentioning
confidence: 99%
“…We have also previously shown that the exciton-polaron annihilation is primarily responsible for the roll-off in solution-processed lanthanide-based OLEDs. 42 In this study, however, our experiments evidence that the applied magnetic field can somehow supress the exciton-polaron annihilation. To better clarify this claim, we also present some example EQE values at different current densities without and with the magnetic field in Table . I.…”
Section: Reduction Of the Efficiency Roll-off A The Exciton-exciton A...mentioning
confidence: 49%
“…In 2019, Shahalizad et al fabricated Nd-1 (Fig. 9 ) based OLEDs by utilizing solution processing method 71 . Co-host EML structure was utilized in designed devices.…”
Section: El Mechanisms and Processes Of Re Complexesmentioning
confidence: 99%